The Evaluation of Radiologic Angular Measurements in Patients with Foot Pain - Deniz, Gulnihal; Kaya, Arzu; Ercan, Zubeyde; Kavakli, Ahmet; Ogeturk, Murat (Amer Podiatric Med Assoc, 2020)
Background: The aim of this study was to investigate the relationship between foot deformities by comparing foot radiographs of patients with complaints of foot pain with those of healthy individuals. Methods: The study included 30 patients with pes cavus, 30 patients with pes planus, 30 patients with calcaneal spur, and 30 controls aged 30 to 60 years. All participants underwent measurement of right and left foot length; metatarsophalangeal width; and calcaneal pitch (CA), talohorizontal (TA), talometatarsal (TM), and lateral talocalcaneal (LTC) angles from lateral radiographs. Results: There were no statistically significant differences between all participants regarding sex, age, weight, and body mass index (P>.05). Among patients with clinically diagnosed pes cavus, the diagnostic rate of CA was 100% in both feet, and 83.3% in the right foot and 96.7% in the left foot according to the TM angle. The diagnostic rates of angular measurements in patients with pes planus were as follows: 20% in the right foot and 30% in the left foot depending on the CA angle, 100% in both feet depending on the TM angle, and 66.7% in the right foot and 46.7% in the left foot depending on the LTC angle. A very strong positive correlation was found between the CA and LTC angles in patients with calcaneal spur and pes planus (P<.001); also, statistically significant positive correlation was found between the CA and TA angles (P<.05). The angular measurements in patients with calcaneal spur were found to be consistent with pes planus with a high rate. Conclusions: Angular changes caused by deterioration of foot biomechanics lead to various deformities. Pes planus ranks first among these. Therefore, we believe that radiographic angular measurements in patients presenting with foot pain in addition to clinical evaluation would be useful in considering associated deformities and planning treatments.